Factors that Influence the Quality of Life Among Undergraduate School of Quantitative Sciences (SQS) Students in Universiti Utara Malaysia (UUM) - Md Yusof, Zahayu; Ayob, Maryam Rukayyah Al-Munirah; Amran, Ahmad Shahrizal; Mohamad Norizan, Nor Farah Hanim (Secholian Publication (Kuala Lumpur, Malaysia), 2020)
The concept of quality of life broadly encompasses on how an individual measures the goodness of multiple aspects of their life, as there are number of challenges to develop a meaningful understanding of the quality of life. The purpose of this study is to identify the factors that contribute to the quality of life among undergraduate SQS students. The respondents of this cross-sectional study were 273 undergraduate students from School of Quantitative Sciences, which was selected via convenient and snowball non-probability sampling method. The collection of the primary data was performed using a questionnaire including demographic and quality of life questions. Analysis of the data was conducted through Statistical Package for the Social Sciences (SPSS) version 2.6. All the 32 items are tested for its’ reliability using the Cronbach’s alpha, and KMO’s. The values are 0.891 and 0.876 respectively. According to the results, there are six factors that contribute/ influence the QoL for the undergraduate SQS students that involved in this study, which are family, friends, academic, social wellbeing, physical and financial, and environment. The value of Cronbach alpha for each factor indicates that the reliability of internal consistency is high and reliable and the KMO’s value for the factor pattern is meritorious and the Bartlett's test of sphericity also resulted with a significant value of p < 0.05